Demographical Analysis and Cultural Characteristic to Attract Japanese Tourists to Indonesia - Agita Arrasy Asthu; William Kalua Putra (Binus Business Review, 2021)
Japan is one of the biggest international tourist contributors to Indonesia. However, in recent years, there is a negative growth. It is caused by the demographical change of the Japanese population and outbound. Hence, research about the cultural ethnicity and social conditions affecting international travelers' behavior in tourism activities is needed. The research focused on the segmentation and strategies to attract foreign tourist which Indonesia would carry. The applied research method was a qualitative descriptive approach that utilized secondary data, such as demographical data and cultural characteristics. Data were taken from the Central Bureau of Statistics of the Republic of Indonesia, Ministry of Tourism and Creative Economy of the Republic of Indonesia, World Bank, and Statistics Bureau of Japan. Then, those data were analyzed by a descriptive statistics method. The result intends to formulate a strategy to seek more potential tourist growth from a Japanese market. The result shows four strategic efforts that Indonesia can take to maximize the potential for the arrival of foreign tourists from Japan. The government can consider the increased number of â€œsilver ageâ€ and adult female workers (Joshitabi), which dominate the travelersâ€™ segment to Indonesia, and pay attention to air connectivity and unique cultural characteristic of Japan.